Target preference of Type III-A CRISPR-Cas complexes at the transcription bubble - Tina Y. Liu (Nature Portfolio, 2019)
Type III CRISPR-Cas systems are able to target transcriptionally active DNA sequences in phages and plasmids. Here, the authors reveal the mechanism of the target nucleic acid preference of Type III-A CRISPR-Cas complexes at the transcription bubble by a combination of structural and biochemical approaches.